2019
DOI: 10.3892/mmr.2019.10335
|View full text |Cite
|
Sign up to set email alerts
|

A specific affinity cyclic peptide enhances the adhesion, expansion and proliferation of rat bone mesenchymal stem cells on β‑tricalcium phosphate scaffolds

Abstract: osteonecrosis of the femoral head (onFH) is a common osteological disease. Treatment of onFH prior to the collapse of the femoral head is critical for increasing therapeutic efficiency. Tissue engineering therapy using bone mesenchymal stem cells (BMSCs) combined with a scaffold is a promising strategy. However, it is currently unclear how to improve the efficiency of BMSC recruitment under such conditions. In the present study, a specific cyclic peptide for Sprague-Dawley rat BMSCs, CTTNPFSLC (known as C7), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Western blotting showed that B7-H3 OE exosomes were able to increase endogenous B7-H3 levels in HMECs by 467% ( p < 0.001) ( Figure 3 C) suggesting B7-H3 may influence the tumor microenvironment through exosomes. UW228 cells, with lower Myc [ 42 ] and B7-H3 levels ( Supplementary Figure S1B ) when incubated with D283 exosomes showed increased B7-H3 while showing a 48% decrease ( p < 0.001) in p-STAT1 levels ( Figure 3 D). These results suggest a receptor-independent role of B7-H3 that may indicate distal and proximal roles of B7-H3 in the cancer microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…Western blotting showed that B7-H3 OE exosomes were able to increase endogenous B7-H3 levels in HMECs by 467% ( p < 0.001) ( Figure 3 C) suggesting B7-H3 may influence the tumor microenvironment through exosomes. UW228 cells, with lower Myc [ 42 ] and B7-H3 levels ( Supplementary Figure S1B ) when incubated with D283 exosomes showed increased B7-H3 while showing a 48% decrease ( p < 0.001) in p-STAT1 levels ( Figure 3 D). These results suggest a receptor-independent role of B7-H3 that may indicate distal and proximal roles of B7-H3 in the cancer microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study demonstrated that the specific affinity cyclic peptide D7 could enhance the adhesion, expansion, and proliferation of BMSCs on β -tricalcium phosphate scaffolds [ 31 ]; therefore, we tested the potential therapeutic effects of D7 on DEX-induced BMSCs damage. To our surprise, D7 exhibited a powerful rescue effect against DEX-induced BMSCs damage, as demonstrated by concentration-dependent amelioration of BMSCs proliferation in CCK-8 assays ( Figure 3(a) ) and reduced expression of apoptosis markers, including LDH activity, cleaved-PARP levels, and cleaved-caspase 3 levels (Figures 3(b) – 3(d) ).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we had screened cyclic polypeptide D7 from the cyclic peptide phage display library (Ph.D.-C7C) by phage display technology [ 31 ]. Phage display is a robust, high-throughput screening strategy in which a library of peptide or protein variants is expressed on the outside of a phage virion, and the genetic material encoding each variant is present on the inside of the virion [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found good proliferation and expansion of the stem cells, with potential for use in in vivo bone tissue engineering. Additionally, they saw an increase in activity of the BMSCs with their scaffold [ 68 ]. Another study used carboxymethyl chitosan/alginate 3D scaffold with BMSCs in an osteonecrosis of femoral head (ONFH) rabbit model over 12 weeks.…”
Section: Desired Characteristics Of 3d Scaffoldsmentioning
confidence: 99%